2019
DOI: 10.22146/ijc.38978
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Adsorption Characteristics for Zeolite-Y Templated Carbon

Abstract: The hydrogen adsorption, kinetic and thermodynamic of adsorption onto the zeolite templated carbon (ZTC) were examined at the temperature range of 30-50 °C and ambient pressure. The ZTC was prepared from zeolite-Y template and sucrose carbon precursor by impregnation method and showed its specific surface area of 932 m2/g as well as 0.97 cm3/g for total pore volume. Analysis of physical and chemical characteristics for materials were performed using XRD, SEM, TEM and N2 isotherm. The results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Previously, it was assumed that the difference in CO 2 and H 2 separation behaviour on this membrane was owing to filler characteristic toward permeating gas and filler position on the membrane surface. First of all, as described by Nishihara et al [ 36 ], ZTC was already widely used in the gas adsorption process involving H 2 [ 38 , 63 ], CO 2 [ 42 , 43 ] and CH 4 [ 36 , 64 ]. It was revealed that at ambient temperature and pressure, ZTC is more active toward CO 2 when compared with the H 2 and CH 4 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was assumed that the difference in CO 2 and H 2 separation behaviour on this membrane was owing to filler characteristic toward permeating gas and filler position on the membrane surface. First of all, as described by Nishihara et al [ 36 ], ZTC was already widely used in the gas adsorption process involving H 2 [ 38 , 63 ], CO 2 [ 42 , 43 ] and CH 4 [ 36 , 64 ]. It was revealed that at ambient temperature and pressure, ZTC is more active toward CO 2 when compared with the H 2 and CH 4 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, making this material fits the required properties for the gas separation membrane. Previously, ZTC has decent CO 2 and H 2 adsorption capacity indicating good affinity towards the respective gas [ 37 , 38 ]. Thus, the gas flow behaviour needs to be controlled so that the adsorption of the stated gas can be avoided to improve the selectivity value.…”
Section: Introductionmentioning
confidence: 99%
“…In fact since 2018 there exist only nine journal articles on the subject of capture/storage of these molecules in ZTCs. 14,[258][259][346][347][348][349][350][351] Furthermore, of these papers two are based on simulations of hypothetical optimized ZTCs. 259,346 While these provide insights into what an optimal ZTC structure might be for these applications, they do not provide novel methods for modulating ZTC porosity.…”
Section: Zeolite Templated Carbonsmentioning
confidence: 99%
“…Wijiyanti et al produced a ZTC with moderate surface area (932 m 2 g À1 ) and pore volume (0.97 cm 3 g À1 ) with hierarchical porosity using sucrose dissolved in H 2 SO 4 , resulting in a material which allows rapid ingress of H 2 (at 30-50 1C and 1 bar) into the porous structure. 346 While the bulk of the literature has focused on using pristine carbon sources in synthesis of ZTCs, Musyoka et al found that a 'dirty' source, namely the pyrolysis gases from used tyres can be used as a CVD vapour (see Table 5). The vapour is composed primarily of small aromatic molecules.…”
Section: Zeolite Templated Carbonsmentioning
confidence: 99%
“…Gas adsorption (physisorption) in porous solids can be used in industrial processes such as oxygen (and argon) separation from air [1][2][3][4], sweetening of natural gas, upgrading of (landfill) biogas [5][6][7][8] and purification of hydrogen obtained from synthesis gas (syngas) or from steam reformation of hydrocarbons [9][10][11], to name only a few examples. Other (prospective) applications include post-combustion carbon dioxide capture from the flue gas of coal fired power stations [12][13][14][15], indoor air purification, e.g., in submarines and manned spacecraft [16][17][18][19], and the use of porous solids for (alternative) hydrogen or methane fuel storage and delivery in the transportation sector [20][21][22][23][24][25][26][27][28][29][30][31][32], including the advent of hydrogen fuelled drones and (possibly) airplanes [33][34][35][36]. For gas separation and purification the gas adsorbent units are frequently operated in a transient mode, which involves alternative gas adsorption-desorption cycles referred to as temperature swing (TSA) or pressure swing (PSA) adsorption, depending on the strategy used to regenerate the porous adsorbent [10,13].…”
Section: Introductionmentioning
confidence: 99%